Pengaruh Human Capital Investment terhadap Employee Performance pada Perguruan Tinggi Swasta di Kabupaten Garut - Hadi Sunyata (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Employee performance is a key factor in determining the success of private higher education institutions in facing competition and increasing demands for educational quality. One strategy considered effective in improving employee performance is organizational investment in human capital development, known as human capital investment. This study aims to analyze the effect of Human Capital Investment on Employee Performance at private higher education institutions in Garut Regency. This research adopts a quantitative approach with an explanatory research design. Data were collected through the distribution of questionnaires to lecturers and educational staff at private universities in Garut Regency, with a total of 109 respondents. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results of the analysis indicate that Human Capital Investment has a positive and significant effect on Employee Performance. These findings suggest that investments in training and development, competency enhancement, and career development play a strategic role in improving the quality and productivity of employee performance. Furthermore, the evaluation of the structural model shows a high coefficient of determination, indicating that Human Capital Investment has very strong predictive power for Employee Performance. The large effect size value also demonstrates that the influence of Human Capital Investment is not only statistically significant but also has substantial practical implications. This study contributes theoretically by strengthening human capital theory within the context of private higher education institutions and provides practical implications for higher education managers in formulating human resource development policies oriented toward performance improvement. Therefore, Human Capital Investment should be viewed as a long-term strategic investment to enhance employee performance and support the sustainability of private higher education institutions.